Determination of Beryllium and Tin in Beryllium Ore by Inductively Coupled Plasma-Mass Spectrometry with Alkali Fusion - Xuedong CHANG; Jing DU; Wenming SUN; Guoqiang XU; Amina HOJI; Ruirui DONG (Yankuang ceshi)
Due to the complex composition of rare metal minerals and the diversity of mineral components, the existing mass spectrometry methods for the determination of beryllium mainly focus on the analysis of low content beryllium in geological samples or ore samples, and rarely study and analyze the associated insoluble tin element in beryllium ores. A method for simultaneous determination of insoluble elements beryllium and tin in beryllium ores with high grade beryllium ore and associated high tin content in Dahongliutan, Xinjiang was established. The strong complex decomposition ability of molten sodium peroxide at high temperature was used to destroy the solid crystal lattice in the mineral, so that the target object was converted into soluble salt and extracted. The salt content of the sample matrix was reduced by 10 times dilution to ensure the long-term measurement stability of RSD below 5%. The matrix matching of the calibration curve was performed and determined by inductively coupled plasma-mass spectrometry. The linear relationship between beryllium and tin was good in the concentration range of 5−2000ng/mL, and the correlation coefficients were greater than 0.999. The detection limits of beryllium and tin were 0.20μg/g and 0.17μg/g respectively. High measurement stability (RSD)≤5%, the upper limit of measurement of beryllium oxide was 5.6%, tin was 2%. Compared with the existing methods, this method has a wide linear range and is suitable for the analysis of beryllium and tin in various high grade beryllium ores. The established method was applied to polymetallic rare metals such as high-grade beryllium ore in Dahongliutan, Xinjiang, and it was found that the precision of the samples with beryllium oxide content above 0.85% and tin content above 0.078% was good. This method is also suitable for the determination of other rare elements such as lithium, rubidium, cesium, niobium, tantalum and rare earth in beryllium ores.